The effect of green products on sustainable tourism through green marketing in natural tourism destinations in Garut, West Java - Yudawisastra, Helin; Burhanudin, Jajang; Samoedra, Artarina D.; Voda, Mihai (International Journal of Green Tourism Research and Applications, 2023)
This research aimed to see the influence of green products on sustainable tourism through green marketing in Garut, West Java, Indonesia. Garut has many tourist destinations, both natural and artificial. Awareness of environmental issues has created new markets that produce environmentally friendly products and services. The method of analysis using multivariate data analysis includes factor analysis with SEM-PLS covariance. The results showed that green products affect sustainable tourism through green marketing as an intervening variable. More awareness is needed for marketing ecosystems with minimal environmental impacts. This research was conducted during the Covid-19 pandemic. The results represent the condition of tourist destinations in Garut affected by the pandemic.